New horizons for adolescent idiopathic scoliosis treatment through PosturalSpine® D’Amanti Method - Francesca Campoli; Maria Chiara Parisi; Antonino Zoffoli; Donatella Di Corrado; Vincenzo Francavilla; Elvira Padua; Giuseppe Messina (European Journal of Translational Myology)
The aim of the study is to compare improvement outcomes in patients (aged between 8 and 18 years old) with idiopathic scoliosis treated with a traditional technique with those treated with an innovative method. The study included 17 participants allocated into two groups: experimental (n = 8) and control (n = 9) groups. The first group was treated with a new method with PosturalSpine® D’Amanti method, twice a week for 30 min per session while the second group was treated with kinesitherapy and traditional tools three times week for 45 min per session. The two groups are similar in the anthropometric characteristics, in baseline Risser index and in the Cobb angles average and no statistically significant differences were found between the two groups. After one year of motor intervention, both treatment groups showed improvements in the progression of scoliotic curves and the PosturalSpine® group showed a significantly higher improvement than the control group. Our results therefore suggest that this new specific method with PosturalSpine® D’Amanti method could play a significant role in improving adolescent idiopathic scoliosis compared to traditional exercises.